Actinyl-cation interactions: experimental and theoretical assessment of [Np(vi)O2Cl4]2− and [U(vi)O2Cl4]2− systems. Issue 24 (29th May 2019) - Bjorklund, Jennifer L.; Pyrch, Mikaela M.; Basile, Madeline C.; Mason, Sara E.; Forbes, Tori Z.
Abstract : Interactions between the Li + cation and the neptunyl(vi ) oxo observed in both solid state and aqueous solutions. Abstract : The interaction of the actinyl (AnO2 2+ ) oxo group with low-valent cations influences the chemical and physical properties of hexavalent actinides, but the impact of these intermolecular interactions on the actinyl bond and their occurrence in solution and solid state phases remain unclear. In this study, we explore the coordination of alkali cations (Li +, Na +, K + ) with the [NpO2 Cl4 ] 2− coordination complexes using single-crystal X-ray diffraction, Raman spectroscopy, and density functional theory (DFT) calculations and compare to the related uranyl system. Three solid-state coordination compounds ([Li(12-crown-4)]2 [NpO2 Cl4 ] (LiNp ), [Na(18-crown-6)H2 O]2 [NpO2 Cl4 ] (NaNp ), and [K(18-crown-6)]2 [NpO2 Cl4 ] (KNp ) have been synthesized and characterized using single-crystal X-ray diffraction and Raman spectroscopy. Only Li + cations interact with the neptunyl oxo in the solid-state compounds and this results in a red-shift of the NpO2 2+ symmetric stretch (ν1 ). Raman spectra of Np(vi ) solutions containing lower Li + concentrations display a single peak at ∼854 cm −1 and increasing the amount of Li + results in the ingrowth of a second band at 807 cm −1 . DFT calculations and vibrational analysis indicate the lower frequency vibrational band is the result of interactions between the Li + cation and the neptunyl oxo. Comparison to the related uranyl system shows similar interactions occur in the solid state, but subtle differences in the actinyl-cation modes in solution phase.